2019
DOI: 10.3390/ani10010015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of B-Wave Ultraviolet Supplementation Using Light-Emitting Diodes on Caged Laying Hens during the Later Phase of the Laying Cycle

Abstract: Caged laying hens are prone to calcium deficiencies, resulting in osteoporosis and egg quality deterioration during the later phase of the laying cycle. Fluorescent light and light-emitting diodes (LEDs), which are widely used in poultry houses now, are both deficient in ultraviolet (UV) light, the lack of which is detrimental to chickens’ welfare and health. This study was conducted to investigate the effects of UVB light supplementation using LEDs on the bone traits, blood parameters, laying performance, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
13
1
Order By: Relevance
“…Research into UV impacts on skeletal health for hens found that UVB exposure of 2 or 3 h daily increased the bone mineral density of older laying hens relative to only 1 h or no UVB supplementation (Wei et al, 2020). However, effects on bone area and bone mineral content were inconsistent among treatment groups across age (Wei et al, 2020).…”
Section: Body Growth Physiology and Skeletal Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into UV impacts on skeletal health for hens found that UVB exposure of 2 or 3 h daily increased the bone mineral density of older laying hens relative to only 1 h or no UVB supplementation (Wei et al, 2020). However, effects on bone area and bone mineral content were inconsistent among treatment groups across age (Wei et al, 2020).…”
Section: Body Growth Physiology and Skeletal Healthmentioning
confidence: 99%
“…Research into UV impacts on skeletal health for hens found that UVB exposure of 2 or 3 h daily increased the bone mineral density of older laying hens relative to only 1 h or no UVB supplementation (Wei et al, 2020). However, effects on bone area and bone mineral content were inconsistent among treatment groups across age (Wei et al, 2020). Assessment of serum samples showed no impacts across the 8-week trial duration on 25(OH)D 3 and P changes across time were similar across all treatment groups (Wei et al, 2020).…”
Section: Body Growth Physiology and Skeletal Healthmentioning
confidence: 99%
“…Preference testing of indoor-housed chickens indicates both laying hen chicks and broilers prefer the UVA spectrum in comparison with lights with no UVA component ( Kristensen et al., 2007 ; Liu et al., 2018 ). UVA and/or UVB light supplementation can increase behavioral activity, reduce fear responses, improve bone composition, and improve egg production ( Sobotik et al., 2020 ; Wei et al., 2020 ). However, these previous studies have typically used low levels of UV supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…PCR-SSCP has been used for several traits of animals such as wool characteristics [ 23 ], milk production traits [ 24 ], profile of sheep fatty acids [ 25 ], detection of Escherichia coli in the black swan [ 26 ], growth and carcass traits in lambs [ 27 ], reproductive traits in cattle [ 28 ], egg production traits in hens [ 29 ], body weight traits on chicken [ 30 32 ], gene study for fat-tailed and nonfat-tailed sheep [ 33 ], serotyping dichelobacter nodosus [ 34 ], mitochondrial diversity role in the productivity of quails [ 35 ], miR-9 gene affects litter size in goats [ 36 ], mutations in porcine [ 37 ], prolactin gene and association with egg production in ducks [ 38 ], wool fibre diameter in ewes [ 39 ], lactoferrin gene affects milk content in buffaloes [ 40 ], milk traits in yaks [ 41 ], association between MyoG gene and egg quality [ 42 ].…”
Section: Other Applicationsmentioning
confidence: 99%